Виражальні функції алегорії у поетиці Т. Г. Шевченка - Моклиця, Марія; Moklytsya, Mariya (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті йдеться про місце і роль алегорії у поетиці Шевченка. Розглядаються ліричні твори, написані в процесі емоційного самовираження. Здатність алегорії унаочнювати абстрактні категорії у формі простих виразних ілюстрацій із життя Шевченко використав як спосіб об’єктивації складних психологічних станів і експресивного впливу на читача. In article it is a question of a place and an allegory role in Shevchenko poetics, according to the author insufficiently studied and estimated. Confusion examples between a symbol and allegory, ignoring of specifics of language of images are critically reviewed. The emphasis that since baroque theater the allegory carries out not only didactic, but also expressive, expressional function is placed. Contrary to tradition to give satirical works as examples of allegory of Shevchenko, in article the lyrical works written in the course of emotional self-expression are considered. Ability of allegory to embody abstract categories in the form of simple and expressive illustrations from life Shevchenko used as a way of an objectivization of difficult mental conditions and expressional influence on the reader.
Expressive function of allegory in T. G. Shevchenko poetics
Keywords: алегорія; персоніфікація; символ; ліричне самовираження; allegory; personification; symbol; lyrical self-expression; expression